DAMPAK PEMBELAJARAN DARING BAGI SISWA SEKOLAH DASAR SELAMA COVID-19 - Ria Puspita Sari; Nabila Bunnanditya Tusyantari; Meidawati Suswandari (Prima Magistra: Jurnal Ilmiah Kependidikan, 2021)
This study aims to know the impact of online learning experienced by teachers and students during the elevate Covid-19 pandemic. This study uses qualitative research, which collects data information using interview techniques, namely to find data about relevant matters. The research subjects were students of SD N Sugihan 03, Bendosari. The results showed that the learning process during the pandemic changed by using a long distance network. This impacts teachers because of a lack of ability to provide learning materials and an annoyance of the learning process that causes the unexpected purpose of learning to go unfulfilled. So that it makes the material incomplete and the use of learning media in online learning is not optimal. Student assessment is also constrained by mere cognitive assessments.